Discursive Practice in Online Learning by Using Zoom Meeting on COVID-19 - Anipon, Puput (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
Since November 2019 COVID-19 virus spread, all activity chance totals especially in Education. Especially in Indonesia applied online learning, the famous application use is Zoom Meeting. I’m as researcher interested analyze how interaction and communication teacher and student in Zoom application, then want find out how Zoom application in learning media present the discursive practice especially between teacher and student, last how student and teacher construct discursive practice use Zoom application. This research aims to find out how discursive practice present in full online class, especially in English class by using Zoom application. This descriptive qualitative study used interview and observation methodology. Twenty six students from English Language Education Study Program, Magister Program of UNP academic year 2021 participated in this study. Based on observed conducted by researcher in class A and B that use Zoom platform in full online learning toward discursive practice. Researcher found discursive practice can present in the class, although in virtual class. Discursive practice in online class by using Zoom application beyond expectation lecturer and student communicate and interaction well with menu that provide by zoom. It can conclude by researcher that the discursive practice can present although in virtual class.